Ultrasound scanning in the detection of hepatic fibrosis and steatosis. Issue 6512 (4th January 1986) - Saverymuttu, S H; Joseph, A E; Maxwell, J D
Abstract : Hepatic steatosis and fibrosis produce abnormal echo patterns on ultrasound scanning, but the potential of ultrasound scanning for diagnosing these conditions in routine clinical practice is uncertain. A prospective comparative study of 85 patients with histologically assessed liver conditions was performed, and specificity was assessed in 76 patients with functional bowel disease who were presumed to have normal livers. Histological examination showed steatosis ranging from mild to severe in 48 patients and fibrosis ranging from increased fibrous tissue to established cirrhosis in 35 patients. Ultrasound scanning accurately identified steatosis, recognising 45 cases (sensitivity 94%) with a specificity of 84%. Fibrosis was less reliably detected (sensitivity 57% and specificity 88%). Of the 50 patients with alcoholic liver disease, 47 (94%) yielded abnormal results on scanning. In the 76 patients with functional bowel disease there was only one false positive result, giving a specificity of 99% in this group. As hepatic steatosis is the earliest change in alcoholic liver disease and seems to be of prognostic importance for the development of cirrhosis, ultrasound scanning provides an effective screening procedure, particularly in the occult alcoholic, who often presents with non-specific gastrointestinal complaints.